Frequency, Risk Factors, and Outcomes of Vancomycin-Resistant Enterococcus Colonization and Infection in Patients with Newly Diagnosed Acute Leukemia: Different Patterns in Patients with Acute Myelogenous and Acute Lymphoblastic Leukemia. (5th January 2015) - Ford, Clyde D.; Lopansri, Bert K.; Haydoura, Souha; Snow, Greg; Dascomb, Kristin K.; Asch, Julie; Bo Petersen, Finn; Burke, John P.
<x content-type="archive" xml:space="preserve">Abstract</x> OBJECTIVE To determine the frequency, risk factors, and outcomes for vancomycin-resistant Enterococcus (VRE) colonization and infection in patients with newly diagnosed acute leukemia. DESIGN Retrospective clinical study with VRE molecular strain typing. SETTING A regional referral center for acute leukemia. PATIENTS Two hundred fourteen consecutive patients with newly diagnosed acute leukemia between 2006 and 2012. METHODS All patients had a culture of first stool and weekly surveillance for VRE. Clinical data were abstracted from the Intermountain Healthcare electronic data warehouse. VRE molecular typing was performed utilizing the semi-automated DiversiLab System. RESULTS The rate of VRE colonization was directly proportional to length of stay and was higher in patients with acute lymphoblastic leukemia. Risk factors associated with colonization include administration of corticosteroids (P=0.004) and carbapenems (P=0.009). Neither a colonized prior room occupant nor an increased unit colonization pressure affected colonization risk. Colonized patients with acute myelogenous leukemia had an increased risk of VRE bloodstream infection (BSI, P=0.002). Other risk factors for VRE BSI include severe neutropenia (P=0.04) and diarrhea (P=0.008). Fifty-eight percent of BSI isolates were identical or related by molecular typing. Eighty-nine percent of bloodstream isolates were identical or related to stool isolates identified by surveillance cultures. VRE BSI was associated with increased costs (P=0.0003) and possibly mortality. CONCLUSIONS VRE colonization has important consequences for patients with acute myelogenous leukemia undergoing induction therapy. For febrile neutropenic patients with acute myelogenous leukemia, use of empirical antibiotic regimens that avoid carbapenems and include VRE coverage may be helpful in decreasing the risks associated with VRE BSI. Infect Control Hosp Epidemiol 2015;36(1): 47–53